Family Support and Exclusive Breastfeeding: The Mediating Role of Breastfeeding Self-Efficacy - Rochmawati Rochmawati; Qorry Wahyuni Septica; Wina Chairunnisa (Yayasan Ahmad Mansyur Nasirah, 2026)
Family support is widely acknowledged as a key determinant of breastfeeding; however, the psychological mechanism linking it to exclusive breastfeeding remains inadequately examined in Indonesia, as no published study has formally tested breastfeeding self-efficacy as a mediator using path analysis frameworks. This study aimed to analyze the mediating role of breastfeeding self-efficacy in the relationship between family support and exclusive breastfeeding among postpartum mothers. A cross-sectional analytical study was conducted with 250 postpartum mothers in Tangerang City and Regency, recruited through purposive sampling across multiple healthcare settings. Data were collected using two validated instruments and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM), with indirect effects examined through indirect effect analysis. Family support had no significant direct effect on exclusive breastfeeding (β = 0.097; p = 0.422), yet strongly predicted breastfeeding self-efficacy (β = 0.887; p < 0.001). Breastfeeding self-efficacy significantly predicted exclusive breastfeeding (β = 0.761; p < 0.001), and the indirect effect was confirmed (β = 0.675; p < 0.001), indicating full mediation. The model explained 45.1% of variance in exclusive breastfeeding and 78.6% in breastfeeding self-efficacy, though causal inference remains constrained by the cross-sectional design. These findings demonstrate that family support promotes exclusive breastfeeding only insofar as it simultaneously strengthens maternal psychological confidence. Exclusive breastfeeding promotion programs should integrate self-efficacy-building components as a core intervention element rather than targeting family support in isolation.